2015
DOI: 10.1002/j.2161-1882.2015.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Parenting: The Effect of an Overbearing Caregiving Style on Peer Attachment and Self‐Efficacy

Abstract: Helicopter parenting, an observed phenomenon on college campuses, may adversely affect college students. The authors examined how helicopter parenting is related to self-efficacy and peer relationships among 190 undergraduate students ages 16 to 28 years. Helicopter parenting was associated with low self-efficacy, alienation from peers, and a lack of trust among peers. Implications are provided for counselors and psychologists in college-and university-based counseling centers to help them to understand and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 39 publications
7
72
2
2
Order By: Relevance
“…This indicates that higher trust among peers will lead to higher academic and social adjustment. The findings of this research is consistent with Van Ingen, Freiheit, Steinfeldt, Moore, Wimer, Knutt, Scapinello, & Roberts (2015) who found that peer trust was positively related to self-efficacy which, in turn was related to social skills and social competence. Tokuno (1983) pointed out that student life was a period of transition that students needed to resolve their issues with peers rather than with family members.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…This indicates that higher trust among peers will lead to higher academic and social adjustment. The findings of this research is consistent with Van Ingen, Freiheit, Steinfeldt, Moore, Wimer, Knutt, Scapinello, & Roberts (2015) who found that peer trust was positively related to self-efficacy which, in turn was related to social skills and social competence. Tokuno (1983) pointed out that student life was a period of transition that students needed to resolve their issues with peers rather than with family members.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…With this combination of parenting dimensions, adolescents would be more likely to experience strong loyalty conflicts toward parents, feeling torn between parents who are experienced as pressuring on the one hand and a desire to gain approval from parents who are generally involved and warm on the other hand. This combination of parenting dimensions is also reminiscent of the concept of overprotective parenting, which has received increasing attention and has also been linked to various maladaptive developmental outcomes in children and adolescents (Segrin, Givertz, Swaitkowski, & Montgomery, ; Segrin, Woszidlo, Givertz, & Montgomery, ; van Ingen et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This combination of parenting dimensions is also reminiscent of the concept of overprotective parenting, which has received increasing attention and has also been linked to various maladaptive developmental outcomes in children and adolescents (Segrin, Givertz, Swaitkowski, & Montgomery, 2015;Segrin, Woszidlo, Givertz, & Montgomery, 2013;van Ingen et al, 2015).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Additionally, individuals with parents who engage in highly controlling, overprotective behaviors have been characterized as being overly needy in terms of seeking attention, approval, and direction from others (Odenweller et al 2014). In addition, they have been found to utilize more ineffective coping skills, express higher levels of narcissism (Segrin et al 2013), and demonstrate lower self-efficacy (van Ingen et al 2015).…”
Section: Introductionmentioning
confidence: 99%